MON-603 GPR142 Expression Levels Were Correlated with Plasma Ghrelin Levels and Heights in Morbidly Obese Patients - Ueda, Yoko (J Endocr Soc, 2020)
Recently, aromatic amino acids, especially tryptophan were discovered to be the strongest ligands for GPR142, which was previously known as an orphan GPCR. GPR142 is expressed in the digestive tract and pancreas in mice and human. Previously we found that GPR142 is highly expressed in the ghrelin-producing cell line, MGN3-1 cells, and that tryptophan strongly stimulated ghrelin secretion in vitro. In this study, we measured the mRNA expression levels of GPR142 in the gastric samples of 6 morbid obese patients undergone laparoscopic sleeve gastrectomy and compared its level with their clinical parameters. GPR142 expression levels were negatively correlated with plasma desacyl ghrelin levels (p=0.011) and positively correlated with heights (p=0.08). The current results that GPR142 expression levels were correlated with plasma desacyl ghrelin levels may confirm the link between GPR142 signal and regulation of ghrelin secretion demonstrated in our in vitro study. Regarding to the correlation with heights, there are some reports that plasma ghrelin levels were inversely correlated with heights in children[1-3], although, as far as we know, there are no reports demonstrating the relationship between plasma ghrelin levels and heights in adults. Considering that ghrelin strongly stimulates growth hormone secretion, GPR142 signaling may have influence on height through regulating ghrelin-growth hormone axis. Conclusion GPR142 mRNA expression levels were negatively and positively correlated with plasma desacyl ghrelin levels and heights in morbid obese adults undergone bariatric surgery. Current results may help understanding the pathophysiological role of GPR142 in the regulation of ghrelin secretion and heights. References 1. MO Camurdan, et al. Endocrine Journal 2006, 53 (4), 479–484 2. HS Park, et al. Metabolism Clinical and Experimental 2005, 54, 925–929 3. Joy C. Bunt,et al. J Clin Endocrinol Metab 2003, 88(8): 3756-3761